Pengaruh Program Remedial dan Gaya Kognitif terhadap Hasil Belajar Matematika - Elly Nurlia Rustiani (Sekolah Pascasarjana Universitas Muhammadiyah Prof. DR. Hamka bekerjasama dengan Himpunan Evaluasi Pendidikan Indonesia (HEPI)., 2016)
Penelitian bertujuan menganalisis perbedaan hasil belajar Matematika siswa yang mengikuti Program Remedial dengan metode Tutor Sebaya dan Pemberian Tugas pada siswa yang bergaya kognitif field independent atau dependent, serta pengaruh program remedial dan gaya kognitif terhadap hasil belajar matematika. Penelitian mengggunakan metode eksperimen, dengan teknik ANAVA dua jalur. Temuannya: (1) Hasil belajar matematika siswa yang diberi program remedial melalui metode tutor sebaya lebih tinggi daripada dengan pemberian tugas. (2) Hasil belajar matematika siswa yang bergaya kognitif field independent lebih tinggi daripada dependent. (3) Terdapat pengaruh interaksi antara program remedial dan gaya kognitif terhadap hasil belajar matematika. (4) Hasil belajar matematika siswa yang bergaya kognitif field independent, dan diberi program remedial melalui metode tutor sebaya lebih rendah daripada melalui metode pemberian tugas. (5) Hasil belajar matematika siswa yang bergaya kognitif field dependent, dan diberi program remedial melalui metode tutor sebaya lebih tinggi daripada melalui metode pemberian tugas. (6) Siswa yang diberi program remedial melalui metode tutor sebaya, hasil belajar untuk siswa yang bergaya kognitif field dependent tidak lebih tinggi daripada field independent. (7) Hasil belajar matematika siswa yang diberi program remedial melalui metode pemberian tugas pada siswa yang bergaya kognitif field independent lebih tinggi daripada field dependent. The study aims to analyze the differences of Mathematics learning achievement of the students who take remedial program with Peer Tutoring methods and Tasks Assigment on the students who have the cognitive style field independent or field dependent as well as the effect of remedial programs and cognitive styles on the Mathematics learning achievement. The reseach uses an experimental method, with two way ANOVA technique. The research findings show that: 1) the students' Mathematics learning achievement taught by remedial programs through peer tutoring method is higher than the method of tasks assigmenet, 2) the Mathematics learning achievement of the students who have cognitive style field independent is higher than those who have cognitive field dependent, 3) there is an interaction effect between the remedial program and cognitive styles on the Mathematics learning achievement, 4) the Mathematics learning achievement of the students who have cognitive field independent style, who was given a remedial program through peer tutoring method is lower than that given method of administration tasks, 5) The Mathematics learning achievement of the students who have cognitive style field dependent taught by a remedial program through peer tutoring method is higher than those taught by method of tasks assignment, 6) The students' mathematics learning achievement taught by a remedial program through the method of peer tutoring to the students who have a field independent cognitive style is lower than those with field dependent cognitive style, 7) the students’ Mathematics learning achievement taught by a remedial program through the method of tasks assignment that have a field independent cognitive style is higher than those who have field dependent cognitive style.